MicroRNA-139 targets fibronectin 1 to inhibit papillary thyroid carcinoma progression - Ye, Ying (Oncol Lett, 2017)
Thyroid cancer is the most common tumour of the endocrine system, and its incidence rate has markedly increased over the past several decades. Aberrantly expressed microRNAs (miRNAs) are reportedly involved in the formation and progression of papillary thyroid carcinoma (PTC) by regulating their target genes. Thus, miRNAs may be potential molecular biomarkers for the prediction and prognosis of PTC, and also as novel therapeutic targets for patients with PTC. miR-139 has recently been reported to be aberrantly expressed in several types of cancer. However, the expression levels, biological functions and the associated molecular mechanism of miR-139 in PTC have not been clearly elucidated. The results of the present study revealed that miR-139 expression was downregulated in PTC tissues and cell lines when compared with adjacent normal tissues and normal human thyroid cells, respectively. The restoration of miR-139 expression suppressed cellular proliferation and invasion in PTC in vitro. In addition, fibronectin 1 (FN1) was identified as a direct target of miR-139 in PTC. Furthermore, FN1 was highly expressed in PTC tissues and negatively associated with miR-139 expression. Moreover, the tumour-suppressive effects of miR-139 overexpression on PTC cells were ameliorated by ectopic FN1 expression. To the best of our knowledge, the present study is the first to demonstrate that miR-139 may serve as a tumour suppressor and serve important roles in inhibiting tumourigenesis by targeting FN1 in PTC cells.